Substituting Small Molecules by Polymers in Light Harvesting Capacitor: Effect on the Coherency of Photogenerated Dipoles - de Lima Filho, Joaquim B.; Günther, Florian [UNESP]; Torres, Bruno Bassi Millan; Miranda, Paulo B. (American Chemical Society (ACS), 2024)
We compare optical and electric properties of multilayered light harvesting capacitors (LHCs) fabricated by layer-by-layer (LbL) polyelectrolyte self-assembly. Electron donor nanolayers were coated from a solution of poly(3-potassium-6-hexanoate thiophene) (P3KHT) while electron acceptor layers were coated from a solution of either a small molecule cationic derivative of N,N′-bis(6-aminohexil)-3,4,9,10-perilenediimide (PDI-6N) or a macromolecule obtained from a polycation of perylenediimide-functionalized polyethileneimine (PDI-PEI). Internal photogeneration of charges was probed via time-resolved transient absorption and continuous-wave photoinduced absorption spectroscopy, while coherent nanodipoles were probed via transient photocurrent measurements, fitted by an analytical equation developed under photophysical principles of LHCs. Data show that charge lifetimes do not depend on external parameters, especially load resistance and pump modulation frequency, while dipole lifetimes depend on load resistance. In addition, it is shown that LHCs based on polymeric acceptor PDI-PEI are more efficient than those based on small molecule acceptor PDI-6N, probably because the smaller acceptor interpenetrates more into the P3KHT polymeric chains, resulting in weaker coherent contribution of photogenerated dipoles to the macroscopic dielectric polarization.